Robust computational framework for wire-mesh sensor potential field calculations - Clifford, Corey E.; MacDonald, Nolan E.; Prasser, Horst-Michael; Kimber, Mark L. (Flow measurement and instrumentation, 2019)
With the development of the next generation of nuclear reactor safety system codes fast underway, increased importance has been placed on enhancing physical closure correlations and amassing representative benchmark-quality experimental data for validation purposes. Wire-mesh sensors, a reputable experimental measurement technique with sufficient spatial and temporal resolution to serve such goals, and related data reconstruction algorithms have been the subject of renewed interest as researchers attempt to characterize their measurement uncertainty. To assist in such investigations, the present work establishes a comprehensive numerical framework with which to quantify the electric potential field around wire-mesh sensors. Using the finite-volume foundations of OpenFOAM, a numerical solution algorithm is developed to predict the transmitted electric current between transmitter and receiver electrodes for both homogeneous and heterogeneous electrical conductivity fields. A detailed verification against seminal numerical calculations and robust validation procedure is included to ensure the accuracy of the proposed methodology. Parametric studies of spherical bubble diameter, lateral crossing position, and spheroidal shape influence are conducted to provide preliminary insights into wire-mesh sensor operation and the suitability of various calibration approaches. Observed trends in the transmitted currents reveal overshoots relative to calibration conditions, which are fundamentally linked to the maldistributed electric potential field in heterogeneous bubbly flows. The present investigation offers a vital first step towards a comprehensive multi-physics model of multiphase flow around a wire-mesh sensor. •Open source finite volume electrical potential field algorithm developed for wire mesh sensors.•Upon validation, code is used to conduct parametric studies.•Impact quantified for bubble size and shape, as well as crossing location.•Overshoots are shown to be tied to maldistribution in electric potential field.